Dampak Pembelajaran Daring Terhadap 3 Pilar Utama Pembangunan Sumber Daya Manusia di Sekolah Dasar Kecamatan Pangean - Mukhzilen, Mukhzilen (ANTHOR: Education and Learning Journal, 2023)
Education in the 21st century based on the The 2015 world economic forum has three main pillars, namely: character, competence, and literacy. Since the outbreak of the Covid 19 pandemic, all aspects of people's lives have experienced very significant changes, including education where education must carry out online learning models. Based on this, researchers are interested in conducting research on elementary school students in Pangean District, Kuantan Singingi Regency to see how far the impact of online learning has on the 3 main pillars of human resource development. This research was conducted in 19 (nineteen) elementary schools located in Pangean District using observation data collection methods, document studies, and online questionnaires while the analytical method used descriptive analysis methods. The results of the study state that there has been a negative impact on the 3 Pillars starting from the Character Pillar has decreased by 91 percent for moral character and 91 percent for performance character, the Competency Pillar has also decreased starting from critical thinking competence which has decreased to 82 percent, creative competence by 76 percent, communicative competence by 82 percent, and collaborative competence by 88 percent while for the literacy pillar, it decreased by 72 percent to the criterion of greatly decreased by 19 percent. Based on this, the researchers concluded that the online model still requires a very long adjustment process from both the school, family, and community environment. This can be seen from the negative impact which is quite significant on the 3 Pillars of Development of Human Resources (HR) for Elementary School Students in Pangean District, Kuantan Singingi Regency.